Manajemen Strategi Guru Menghadapi Kurikulum Merdeka di Sekolah Menengah Pertama - Damayanti, Alvina Dwi; Hasanah, Silviatul; Lestari, Prihatin (JURNAL MANAJEMEN PENDIDIKAN, 2024)
The relationship between management as an important element in educational management with strategy as a way of implementing management has a close relationship. As a unified system, strategic management is indispensable in helping to implement an independent curriculum. The transformation of the implementation of the previous curriculum with the independent curriculum currently implemented by the government has quite specific developments. The use of technology, varied teaching materials and various methods that must be learned well by teachers today.  This study aims to examine teachers' strategic management in dealing with the "Independent Curriculum" in Junior High School (SMP) at Hasanuddin 6 Semarang Junior High School and analyze the obstacles that exist in implementing the "Independent Curriculum". This research is descriptive research with a qualitative approach. Data collection is done through observation, interview and documentation techniques. The data collected was then analyzed qualitatively in three stages; data reduction, data presentation and conclusion drawing. The results showed that there are important things that must be prepared in implementing an independent curriculum at school. Based on the results of the research, strategic management needs to pay attention to 3 aspects, how to plan, provisions in implementation and evaluation forms in an independent curriculum.  As an educational institution that carries out its functions systematically, the most effective form of evaluation is by paying attention to planning, organizing and implementing to minimize failure.